OPTIMALISASI SISTEM PENGELOLAAN PERSAMPAHAN DI IBU KOTA KABUPATEN KEPULAUAN TANIMBAR - Baran Kei Fernando Titirloloby; Stevianus Titaley; Kreisson P. Larwuy (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Saumlaki, the capital of Kepulauan Tanimbar Regency, faces an unoptimized solid waste management system, marked by only one container-type temporary collection point (TPS) and 87 small waste bins serving a population of 10,800, alongside a final disposal site (TPA) still operated through open dumping. These conditions leave approximately 26%, or around 2,971.9 kg, of daily waste generation unmanaged and disposed of illegally across residential areas. This study aims to analyze the existing condition of the waste management system, identify the factors causing its underperformance, and formulate an optimization strategy based on SWOT analysis. A mixed-method approach was applied, combining quantitative and qualitative techniques through field observation, interviews, questionnaires, and document analysis. Qualitative data were validated through data triangulation, while quantitative data from questionnaires were analyzed descriptively and used to weight the SWOT factors. The results show that Saumlaki's waste management system is positioned in Quadrant III (Weakness-Opportunity) with SWOT coordinates of (-0.18; +0.49), indicating that internal weaknesses in infrastructure and budget can be addressed by leveraging external opportunities such as national policy support and grant programs from the Ministry of Environment and Forestry. Referring to SNI 3242:2008, the ideal number of TPS units for a population of 10,800 is five, requiring four additional units planned across four strategic locations. The recommended optimization strategy includes strengthening sorting-based TPS infrastructure, optimizing collection routes, developing the Amtufu landfill toward a sanitary landfill system, drafting a local regulation on 3R-based waste management.